Cheek mucosa territories perfused by perforators from the facial artery. Issue 1 (January 2015) - Coronel-Banda, M.E.; Serra-Renom, J.M.; Lorente, M.; Larrea-Terán, W.P.
Abstract The cutaneous areas perfused by the cutaneous perforators of the facial artery have been well defined. However, the oral mucosal areas perfused by perforators of the facial artery have not been described. We studied 20 hemifaces from 10 cadavers. Perforators between the branching off sites of the labial arteries larger than 0.5 mm were selected and their diameters were measured; the distance between their exit point over the facial artery and the branching-off point from the superior labial artery was also measured. The selected perforators were injected with 1 ml of diluted ink. Both labial arteries were ligated to limit the study to the mucosal perforators from the facial artery. Seventy-four perforators from 20 hemifaces were studied; the mean diameter was 0.58 mm and the mean number per artery was 3.7. The total stained area, a triangle-shaped zone on the cheek, was determined. The more constant perforators larger than 0.5 mm were localized next to the branching-off site of the superior labial artery. With this information, flaps based on the mucosal perforators from the facial artery could be designed.